Banking fragility and distress: an econometric study of macroeconomic determinants - Jarmo Pesola (Bank of Finland, 2005)
The macroeconomic determinants of banking sector distresses in the Nordic countries, Belgium, Germany, Greece, Spain and the UK are analysed using an econometric model estimated on panel data from partly the early 1980s to 2002.The dependent variable is the ratio of banks' loan losses to lending.In addition to the lagged dependent variable, the explanatory variables include a surprise change in incomes and real interest rates, both variables as a separate cross-product term with lagged aggregate indebtedness.The underlying macroeconomic account that this paper puts forward is that loan losses are basically generated by strong adverse aggregate shocks under high exposure of banks to such shocks.The underlying innovations to income and real interest rates are constructed using published macro-economic forecast for these variables.According to the results, high customer indebtedness combined with adverse macroeconomic surprise shocks to income and real interest rates contributed to the distress in banking sector. Loan losses also display strong autoregressive behaviour which might indicate a feedback effect from loan losses back to macroeconomic level in deep recessions.The results can be used in macro stresstesting the banking sector.
URN:NBN:fi:bof-20140807155
Keywords: G21; E44; 330; financial fragility; shock; loan loss; banking crisis